Phase-contrast X-ray imaging based on interferometry - Momose, Atsushi (Journal of synchrotron radiation, 2002)
Phase-contrast X-ray imaging including tomographic configuration using a crystal X-ray interferometer is reviewed. The imaging principle based on phase retrieval is described, and some demonstrations showing its high sensitivity are presented on the observations of animal and human cancerous tissues